(untitled) (American Journal of Humanities and Social Sciences, 2013)
<!–[if gte mso 9]> <![endif]–> Effectiveness of popularization of Marxism in ideological and political theory course is the key for Chinese university students to set up a correct outlook on world, a correct outlook on life and values. As a result of influences of all kinds of factors, there still exist a lot of issues and difficulties in the process of publicizing and educating Marxism in Chinese universities. This requires taking corresponding measures to fulfill popularization of Marxism in ideological and political theory course teaching in universities. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>